The New sailing directory for the island and banks of Newfoundland, the gulf and river of St. Lawrence, Breton Island, Nova Scotia, the Bay of Fundy and the coasts thence to Portland, Boston, Cape Cod, &c. [electronic resource] - Purdy, John, 1773-1843. (London : Printed for R.H. Laurie, 1827)
Includes publisher's list. Electronic reproduction. Mode of access: Internet. 44